2014
DOI: 10.3390/e16063357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anticipation in Individually Motivated Behaviour on Survival and Control in a Multi-Agent Scenario with Resource Constraints

Abstract: Self-organization and survival are inextricably bound to an agent's ability to control and anticipate its environment. Here we assess both skills when multiple agents compete for a scarce resource. Drawing on insights from psychology, microsociology and control theory, we examine how different assumptions about the behaviour of an agent's peers in the anticipation process affect subjective control and survival strategies. To quantify control and drive behaviour, we use the recently developed information-theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Far beyond a simplistic search for "better-performing" models, this again serves as a cognitive aid to build understanding and intuition about how aspects of different models function and behave in different situations. Guckelsberger and Polani (2014), for instance, compared the impact of different variants of empowerment, a popular computational IM (Salge, Glackin, & Polani, 2014), on the social interaction dynamics of a triad of AI agents under resource scarcity and limited observability. In their scenario, an agent's empowerment calculation and action selection requires the agent to anticipate long-run consequences of other agents' behaviour.…”
Section: Advancing Psychology Via Computational Simulationsmentioning
confidence: 99%
“…Far beyond a simplistic search for "better-performing" models, this again serves as a cognitive aid to build understanding and intuition about how aspects of different models function and behave in different situations. Guckelsberger and Polani (2014), for instance, compared the impact of different variants of empowerment, a popular computational IM (Salge, Glackin, & Polani, 2014), on the social interaction dynamics of a triad of AI agents under resource scarcity and limited observability. In their scenario, an agent's empowerment calculation and action selection requires the agent to anticipate long-run consequences of other agents' behaviour.…”
Section: Advancing Psychology Via Computational Simulationsmentioning
confidence: 99%
“…Capdepuy et al [6,7] investigated the interactions between agents that individually attempt to maximize empowerment in a shared environment and found that interesting structures can emerge. Similarly, Guckelsberger and Polani [17] evolved agents for empowerment maximization in a resourcecentric environment which resulted in agents exhibiting biologically plausible behaviors, such as greed and parsimony. Lastly, Clements and Polani [9] introduce the idea of team empowerment.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, we do not need to know about the game's complete mechanics or parameters, but only about how the player's actions affect what they can perceive. Existing studies demonstrate that empowerment is not restricted to single-player games [16,18], and can deal with uncertainty and dynamic game worlds [42].…”
Section: Aggregating Quantities Into Experience Predictionmentioning
confidence: 99%